2017
DOI: 10.1002/tea.21426
|View full text |Cite
|
Sign up to set email alerts
|

The role of high school racial composition and opportunities to learn in students' STEM college participation

Abstract: We analyze longitudinal data from students who spent their academic careers in North Carolina (NC) public secondary schools and attended NC public universities to investigate the importance of high school racial composition and opportunities to learn in secondary school for choosing a science, technology, engineering, and mathematics (STEM) major. We consider school racial composition and opportunities to learn as contexts that shape students' decisions regarding college majors. Results of cross-classified hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…The most innovative companies are 27% more ethnically diverse than are bioeconomy companies. Racial diversity contributes significantly to diversity in thought and decision-making (Galinsky et al, 2015;Bradbury and Kellough, 2008;Bottia et al, 2018). The large difference observed may be attributable to the market area in which they operate and their extent of global business operations.…”
Section: Bioeconomymentioning
confidence: 99%
“…The most innovative companies are 27% more ethnically diverse than are bioeconomy companies. Racial diversity contributes significantly to diversity in thought and decision-making (Galinsky et al, 2015;Bradbury and Kellough, 2008;Bottia et al, 2018). The large difference observed may be attributable to the market area in which they operate and their extent of global business operations.…”
Section: Bioeconomymentioning
confidence: 99%
“…Previous research has shown that school racial and socioeconomic composition have a strong association with opportunities to learn, including social and cultural capital, peer academic and behavioral norms, future expectations (Ready & Silander, 2011), access to high quality teachers (Jackson, 2009;Peske & Haycock, 2006), and the number of AP classes offered (Robinson, 2003). Importantly, these opportunities to learn have significant positive associations with students' college attendance, college achievement, and choice of college major (Anelli & Peri, 2013;Bottia, Mickelson, Giersch, Stearns, Stearns et al & Moller, 2018;Giersch, Bottia, Mickelson, & Stearns, 2016;Harris, 2010;Jackson, 2009;Teranishi & Parker, 2010). Due to secondary schools' importance for STEM preparation, we included several high school characteristics that likely are related to probability of declaring a STEM major and first-year GPA performance.…”
Section: High School-level Variablesmentioning
confidence: 99%
“…Stakeholders consider STEM-focused schools also to be a propitious strategy for closing the racial and gender gaps in STEM "opportunities to learn" and interest gap (Lynch, Behrend, Burton, & Means, 2013;Means, Wang, Young, Peters, & Lynch, 2016). The K-12 context strongly influences the amount of knowledge and interest students have regarding STEM disciplines (Bottia, Mickelson, Giersch, Stearns, & Moller, 2017;Bottia, Stearns, Mickelson, Moller, & Parker, 2015;Bottia, Stearns, Mickelson, Moller, & Valentino, 2015), and therefore shapes, in part, the intellectual development and opportunities for future study and work in these areas. Schools with a STEM focus are expected to help produce students who are interested in science and mathematics.…”
mentioning
confidence: 99%